HPV 16 E5 oncoprotein is expressed in early stage carcinogenesis and can be a target of immunotherapy - Francesca Paolini; Gianfranca Curzio; Marcelo Nazario Cordeiro; Silvia Massa; Luciano Mariani; Fulvia Pimpinelli; Antonio Carlos de Freitas; Rosella Franconi; Aldo Venuti (Taylor & Francis Group, 2017)
HPV16 persistent infection is a well-known condition that precedes human cancer development. High risk HPV E5 proteins cooperate with E6/E7 oncogenes to promote hyper-proliferation of infected cells leading to possible cancer progression. Thus, presence of E5 viral transcripts could be a key marker of active infection and, in turn, a target of immunotherapy. Purpose of the study is to detect E5 transcripts in clinical samples and to explore the activity of novel anti-HPV16 E5 DNA vaccines. HPV transcripts were detected by PCR with specific primers encompassing the splice-donor sites of E5 transcript. For E5-based immunotherapies, 2 E5-based versions of DNA vaccines carrying whole E5 gene or a synthetic multiepitope gene were improved by fusion to sequence of PVX coat protein. These vaccines were challenged with a new luminescent animal model based on C3-Luc cell line. E5 transcripts were detected in clinical samples of women with HPV positive low-grade SIL, demonstrating the validity of our test. In C3 pre-clinical mouse model, vaccine candidates were able to induce a strong cellular immunity as indicated by ELISPOT assays. In addition, E5-CP vaccines elicited strong anti-tumor effects as showed by decreased tumor growth monitored by animal imaging. The tumor growth inhibition was comparable to those obtained with anti-E7 DNA vaccines. In conclusion, detection of E5 transcripts in clinical samples indicates that E5 is a possible target of immunotherapy. Data from pre-clinical model demonstrate that E5 genetic immunization is feasible, efficacious and could be utilized in clinical trials.